2020
DOI: 10.1111/camh.12385
|View full text |Cite
|
Sign up to set email alerts
|

Technology Matters: The human touch in a digital age – a blended approach in mental healthcare delivery with children and young people

Abstract: now recommend digitally delivered therapy in the treatment of depression in children and young people (CYP) (NICE, 2019). However, despite the virtual ubiquity of technology in young people's lives, and good evidence that online treatments can be effective, there remain barriers to real-world implementation. We argue that remote therapist support and blended approaches to therapy will be important models in harnessing the potential of digital technology in CYP mental health."Therapist supported" online interve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 8 publications
1
13
0
Order By: Relevance
“…The literature suggests that evidence-based apps may be efficacious in raising self-awareness, mental health literacy and wellbeing, self-efficacy, and ability to cope [ 96 , 100 , 101 , 102 ]. Online psychological interventions are becoming more prominent in the digital age [ 103 ], rendering numerous positive health outcomes [ 102 , 104 , 105 , 106 , 107 , 108 ], complementing service provision and recognized by governmental health institutions (e.g., National Institute for Health and Care Excellence (NICE) in the UK) [ 109 ]. However, more research is required to determine the comparative effectiveness of these therapies and their components [ 110 ] in improving mental health and wellbeing and rigorous objective evaluation beyond their developers is required.…”
Section: Introductionmentioning
confidence: 99%
“…The literature suggests that evidence-based apps may be efficacious in raising self-awareness, mental health literacy and wellbeing, self-efficacy, and ability to cope [ 96 , 100 , 101 , 102 ]. Online psychological interventions are becoming more prominent in the digital age [ 103 ], rendering numerous positive health outcomes [ 102 , 104 , 105 , 106 , 107 , 108 ], complementing service provision and recognized by governmental health institutions (e.g., National Institute for Health and Care Excellence (NICE) in the UK) [ 109 ]. However, more research is required to determine the comparative effectiveness of these therapies and their components [ 110 ] in improving mental health and wellbeing and rigorous objective evaluation beyond their developers is required.…”
Section: Introductionmentioning
confidence: 99%
“…It was also not possible to distinguish between performances of online or non-online delivered trials from the HTA data set, although it is likely that different types of trial delivery have their own set of challenges. Indeed, some previous studies indicate that online trials are susceptible to specific challenges such as potential breaches to confidentiality through online communication [ 40 ] as well as lack of personalisation and difficulties with rapport building with participants [ 41 ]. Furthermore, it is likely that conducting trials with any online element may be particularly problematic in elderly or very deprived populations, with poor internet access and/or lack of privacy, and thus, we are not advocating online delivery as a blanket approach.…”
Section: Discussionmentioning
confidence: 99%
“…14,27 Research has shown that online telehealth interventions for youth have great potential to improve mental health when they are facilitated by a trained mental health care provider and off er synchro nous sessions that actively build rapport. 28 The results of a systemic review of the impact of online mental health interventions show significant positive effects of online cognitive-behavioural therapy, with adolescents indi cating increased compliance rates when online preven tion and intervention programs incorporate both face to-face web-based interaction between participant and counsellor and web-based support. 14 Another benefi t identified is that online mental health interventions can offer convenient access to quality, evidence-informed re sources, targeting several barriers that many children and youth face when attempting to access mental health in terventions.…”
Section: Online Mental Health Support For Children and Youthmentioning
confidence: 99%
“…Although several apps and online platforms have been developed in the child and youth mental health field, a gap exists in evaluating the effi cacy of these programs. 28 It is crucial that researchers evaluate existing virtual care-delivery programs to ensure inter ventions and programs created for this target population are effective in the Canadian context and meet the unique needs of children and youth in PSP-connected families. Research should focus on identifying key prac tices and strategies in a virtual mental health program for PSP-and military-connected families that will improve access to culturally sensitive and developmentally appro priate support for an increasingly vulnerable population.…”
Section: Future Directionsmentioning
confidence: 99%